2019
DOI: 10.1186/s12957-019-1756-8
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic inflammation and formation of necrosis in the tumor microenvironment influence patient survival after radical surgery for de novo hepatocellular carcinoma in non-cirrhosis

Abstract: Background: Tumor escape mechanisms mediated in the tumor microenvironment can significantly reduce the capacity of the anti-tumor function of the immune system. TIE2-expressing monocytes (TEMs), related angiopoietins, and tumor necrosis are considered to have a key role in this process. We aimed to investigate the abundance and clinical significance of these biomarkers in hepatocellular carcinoma (HCC). Methods: In this retrospective study, 58 HCC patients received surgery with a curative intent. The abundanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…A recent study revealed that the presence of tumor necrosis is associated with an advanced tumor stage, HCC recurrence, and patient survival after curative hepatectomy for HCC [29]. In agreement with these ndings, we also identi ed necrotic HCC to be associated with a high rate of EHR.…”
Section: Analysis Of Factors Associated With Ehrsupporting
confidence: 88%
“…A recent study revealed that the presence of tumor necrosis is associated with an advanced tumor stage, HCC recurrence, and patient survival after curative hepatectomy for HCC [29]. In agreement with these ndings, we also identi ed necrotic HCC to be associated with a high rate of EHR.…”
Section: Analysis Of Factors Associated With Ehrsupporting
confidence: 88%
“…Advanced HCC implicated multiple cellular pathways and played central roles in tumor metastasis and recurrence. Activity signaling cascade in HCC, including Ras/Raf/MEK/ERK and Ras/PI3K/Akt/mTOR, which promotes transcription of genes involved in tumor proliferation [43]. Sorafenib, a TKI (tyrosine kinases inhibitor) drug, was the first multikinase inhibitor authorized for the medicine of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al reported that EHR was more common among patients with vascular invasion, intrahepatic metastasis, and more advanced HCC stages 11 . A recent study revealed that the presence of tumor necrosis was associated with an advanced tumor stage, HCC recurrence, and patient survival after curative hepatectomy for HCC 23 . In agreement with these findings, we also identified that necrotic HCC was associated with a high rate of EHR.…”
Section: Discussionmentioning
confidence: 99%